Disparitas Putusan Hakim Terhadap Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial - Potale, Mutiara; M. Wantu, Fence; Apripari (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study aims to analyze disparities in judges' rulings regarding defamation crimes through social media by comparing Verdict No. 21/Pid.Sus/2020/PN.Lbo (3 months imprisonment) and No. 45/Pid.Sus/2022/PN.Lbo (4 months conditional sentence), using normative legal research methods through comparative analysis of verdicts. The results show that although both cases share similar legal elements under Article 27 paragraph (3) of the ITE Law, with defendants being first-time offenders who expressed remorse, there were significant sentencing disparities in terms of penalty types (immediate vs. conditional) and duration. The findings reveal that these disparities are influenced by three main factors: (1) the flexibility of the ITE Law which lacks minimum sentencing guidelines, (2) judges' subjective considerations based on Article 5 of the Judicial Power Law that account for societal justice values and trial facts, and (3) individual defendant characteristics such as age, legal history, and reconciliation efforts. The study concludes that sentencing disparities result from complex interactions between the ITE Law's unclear sentencing boundaries, judicial discretion, and personal defendant factors, necessitating clearer sentencing guidelines in the ITE Law and more measurable judicial considerations to establish legal certainty.